Pola Praktis Penerjemahan Arab-Indonesia: Bentuk Perubahan Makna - Naimah, Izzatun; Nu’man, Mohammad (Al Maghazi : Arabic Language in Higher Education, 2024)
Translation is a difficult scientific activity. The difficulty becomes even more complex when the translator does not find a way to overcome the problem. This means that the translator lacks mastery of translation theory. The scarcity of theoretical and practical studies on Arabic-Indonesian translation is a distinct issue in the world of Arabic-Indonesian translation. In turn, this leads to a low quality of translation. This study aims to analyze the practical patterns of translating Arabic into Indonesian, specifically in forms of meaning changes, such as narrowing, expansion, and omission of meaning. This research uses a qualitative research method with a literature review, namely collecting data by mastering concepts from various literatures that are associated with studies relevant to issues concerning practical patterns of Arabic-Indonesian translation. This research emphasizes the importance of a deep understanding of both languages, including linguistic and cultural aspects, in producing accurate and communicative translations. This study contributes to the field of translation studies by offering insights into effective strategies for overcoming the challenges of meaning shifts. These results are expected to serve as a guide for translators and academics in improving the quality of Arabic-Indonesian translation.